BOA: A partitioned view of genome assembly - An, Xiaojing; Ghosh, Priyanka; Keppler, Patrick; Kurt, Sureyya Emre; Krishnamoorthy, Sriram; Sadayappan, Ponnuswamy; Rajam, Aravind Sukumaran; Çatalyürek, Ümit V.; Kalyanaraman, Ananth (iScience, 2022)
De novo genome assembly is a fundamental problem in computational molecular biology that aims to reconstruct an unknown genome sequence from a set of short DNA sequences (or reads) obtained from the genome. The relative ordering of the reads along the target genome is not known a priori, which is one of the main contributors to the increased complexity of the assembly process. In this article, with the dual objective of improving assembly quality and exposing a high degree of parallelism, we present a partitioning-based approach. Our framework, BOA (bucket-order-assemble), uses a bucketing alongside graph- and hypergraph-based partitioning techniques to produce a partial ordering of the reads. This partial ordering enables us to divide the read set into disjoint blocks that can be independently assembled in parallel using any state-of-the-art serial assembler of choice. Experimental results show that BOA improves both the overall assembly quality and performance. [Display omitted] •A graph/hypergraph partitioning based method to improve assembly quality and runtime•Bucketing and graph/hypergraph partitioning to partition reads into blocks•Each block is then independently assembled using any standalone assembler•Hypergraph variant produces more precise contigs and is faster than state-of-the-art assemblers Genomics; Bioinformatics; High-performance computing in bioinformatics; Algorithms.